2004
DOI: 10.1002/app.20474
|View full text |Cite
|
Sign up to set email alerts
|

Development of calibration models for estimation of monomer concentration by Raman spectroscopy during emulsion polymerization: Facing the medium heterogeneity

Abstract: ABSTRACT:This work compares different calibration models for the estimation of monomer concentrations by Raman spectroscopy during semicontinuous emulsion copolymerization reactions. The limitations of these models are discussed in terms of a complex reaction, namely the copolymerization of vinyl acetate and butyl acrylate, whose monomers present overlapping Raman spectra, especially the CϭC stretching band. Additionally, the copolymerization was monitored in a spectroscopic setup arranged for fast spectral ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…The C-H aromatic bond present in both styrene monomer and polystyrene did not change along the reaction and could be used as an internal reference peak to normalize the data, thus filtering the noise fluctuations of the collected spectra. [8,32] The normalized area was calculated using the ratio between the area of the double bond peak (at 1631 cm…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The C-H aromatic bond present in both styrene monomer and polystyrene did not change along the reaction and could be used as an internal reference peak to normalize the data, thus filtering the noise fluctuations of the collected spectra. [8,32] The normalized area was calculated using the ratio between the area of the double bond peak (at 1631 cm…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…In special, in hetero geneous polymerization processes, these techniques can be useful to simultaneous monitoring different variables, such as those related to chemical changes in the reaction medium (e.g., monomer conversion) as well as those related to the physical changes in the particles (e.g., changes in particle size). [8][9][10][11][12][13][14][15][16][17][18][19] Spectroscopy-based sensors in combination with optical fibers allow the inline measurements and real-time monitoring of polymerization processes. [18][19][20][21][22][23][24][25][26][27][28][29] For the particular case of heterogeneous polymerization reactions, Raman and NIR spectra show two distinct regions, as identified in Figure 1, where different characteristics can be explored: (a) the spectral region that permits to identify chemical information related to the vibrations of the main bonds present in the components (monomer and polymer) and (b) the spectral region with physical information, where the spectrum baseline variation is related to physical properties, such as particle diameter in this case.…”
Section: Introductionmentioning
confidence: 99%
“…Pinto and coworkers100, 427–435 have also made several contributions in this area. Santos et al100 reviewed the uses of NIR spectroscopy in polymerization process monitoring and control with emphasis on solution, suspension and emulsion polymerization processes.…”
Section: On‐line Sensors For Polymer Property Trajectory Monitoringmentioning
confidence: 99%
“…Nogueira et al429 developed a new method based on the simultaneous use of NIR spectroscopy and viscometry to monitor and control weight‐average molecular weight of polyurethanes produced by a solution step‐growth polymerization process. Reis et al430, 436 used NIR spectroscopy to estimate conversion and copolymer composition. They also found that the polymer PS was correlated with the NIR spectra.…”
Section: On‐line Sensors For Polymer Property Trajectory Monitoringmentioning
confidence: 99%
“…Obtaining and establishing reference values for these samples often is one of the hardest parts of a process analytical technology project, regardless of the technique selected. A separate paper compares prediction results using models built using process -generated versus synthetic samples [208] . Reis et al present two cases where synthetic samples were used successfully to build predictive models of monomer concentration during butyl acrylate and vinyl acetate homopolymerizations [207] .…”
Section: Polymerizationmentioning
confidence: 99%